2016
DOI: 10.1534/g3.116.035725
|View full text |Cite
|
Sign up to set email alerts
|

X Chromosome Crossover Formation and Genome Stability inCaenorhabditis elegansAre Independently Regulated byxnd-1

Abstract: The germ line efficiently combats numerous genotoxic insults to ensure the high fidelity propagation of unaltered genomic information across generations. Yet, germ cells in most metazoans also intentionally create double-strand breaks (DSBs) to promote DNA exchange between parental chromosomes, a process known as crossing over. Homologous recombination is employed in the repair of both genotoxic lesions and programmed DSBs, and many of the core DNA repair proteins function in both processes. In addition, DNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 65 publications
(113 reference statements)
2
19
0
Order By: Relevance
“…This study showed that recombination is largely suppressed in the central and distal chromosomal regions and enriched in what is considered the chromosome “arms” in C. elegans (Rockman and Kruglyak 2009), although the position of these crossovers varies widely on the autosomes (Rockman and Kruglyak 2009). Moreover, multiple studies have shown that during oogenesis, DSB formation and crossing over requires histone acetylation and methylation modifications (Wagner et al 2010; McClendon et al 2016; Bessler et al 2007, 2010; Reddy and Villeneuve 2004). Currently, it is unclear whether post-translation modifications of histones are required for DSB formation and crossing over during spermatogenesis.…”
Section: Pachytene: Establishment Of Crossovers Between Homologsmentioning
confidence: 99%
“…This study showed that recombination is largely suppressed in the central and distal chromosomal regions and enriched in what is considered the chromosome “arms” in C. elegans (Rockman and Kruglyak 2009), although the position of these crossovers varies widely on the autosomes (Rockman and Kruglyak 2009). Moreover, multiple studies have shown that during oogenesis, DSB formation and crossing over requires histone acetylation and methylation modifications (Wagner et al 2010; McClendon et al 2016; Bessler et al 2007, 2010; Reddy and Villeneuve 2004). Currently, it is unclear whether post-translation modifications of histones are required for DSB formation and crossing over during spermatogenesis.…”
Section: Pachytene: Establishment Of Crossovers Between Homologsmentioning
confidence: 99%
“…Since HIM-5 and XND-1 exhibit the same autosomal localization and loss at late pachytene as OEF-1, we analyzed the broods of oef-1; him-5 and xnd-1; oef-1 double-mutants. Given that xnd-1 mutants have pleiotropic germline defects and show stochastic sterility in later generations (McClendon et al 2016), we focused our analyses on the broods of xnd-1 M+Z-parents. We found that oef-1 partially rescued the him-5 percentage of males from 37.53 to 30.24% (P , 0.0001, Fisher's exact test) (Table 1).…”
Section: Oef-1 Associates With Germline-expressed Genes and Localizesmentioning
confidence: 99%
“…First, silencing of unsynapsed chromatin has been observed in C. elegans 32 , so the basic mechanism of MSUC exists. Second, disruption of sex chromosome integrity in mammals leads to silencing of synapsed parts of autosomes and sex chromosomes in pachytene [34][35][36] Like initiation of silencing, other meiotic processes are also executed differently on the X chromosome than on autosomes in hermaphroditic worms [81][82][83][84][85][86] . These differences suggest that the X chromosome is marked differently than the autosomes, and, indeed, previous reports indicate that the X chromosomes are enriched with different histone modifications than are autosomes 26,32,81,82,87 .…”
Section: Discussionmentioning
confidence: 99%
“…Like initiation of silencing, other meiotic processes are also executed differently on the X chromosome than on autosomes in hermaphroditic worms 8186 . These differences suggest that the X chromosome is marked differently than the autosomes, and, indeed, previous reports indicate that the X chromosomes are enriched with different histone modifications than are autosomes 26, 32, 81, 82, 87 . Thus, an epigenetic mechanism may regulate silencing and its dependence on integrity.…”
Section: Discussionmentioning
confidence: 99%